2016
DOI: 10.1002/lsm.22575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anisotropy and drying of costal cartilage on its optical transmittance in laser reshaping of implants with 1, 2, and 3 mm in thickness

Abstract: The effect of structural anisotropy of costal cartilage reveals itself in the increasing scattering of IR radiation with λ = 1,560 nm passing crosswise the collagen orientation when tissue water content is decreased. The radiation with λ = 1,560 nm is effective to perform the reshaping for cartilage of 1-3 mm in thickness; however, for 3 mm, the residual mechanical stress should be taken into account. Lasers Surg. Med. 48:887-892, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For transferring these novel technologies from tests on phantoms and excised tissue samples to in vivo ophtalmological applications, a key point is to ensure safety of the treatment (avoiding overheating) and the possibility to visualize dynamic strains in real time together with the resultant shape of the tissue. Similar issues are very important in the fabrication of cartilaginous implants (typically with ~mm-scale thickness) for otolaryngology [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For transferring these novel technologies from tests on phantoms and excised tissue samples to in vivo ophtalmological applications, a key point is to ensure safety of the treatment (avoiding overheating) and the possibility to visualize dynamic strains in real time together with the resultant shape of the tissue. Similar issues are very important in the fabrication of cartilaginous implants (typically with ~mm-scale thickness) for otolaryngology [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The stable semicircle shape of cartilage reflects the tracheal curvature and is aimed to prevent airway narrowing, which is the life-threatening adverse effect in trachea stenosis surgery [14]. Analyzing the obtained effect for implants of different thickness we showed that well-controlled heating through the whole thickness of an implant is crucial for the new shape stability [15]. Simultaneously, the very local heating of cartilage by separate laser spots is needed to avoid thermal injury of matrix and cells [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…But the attempts to heat the deep tissue layers of thicker implants may cause the superficial burn and substantially disturb the safety of the procedure. On the contrary, thin cartilage implants transmit a lot of laser energy and possess high residual stress that disrupts the stability of the new shape .…”
Section: Introductionmentioning
confidence: 99%